Improve On Time Delivery: A Case Study At Jm Flour Mill - Ong, Wen Ing (2014)
On time delivery is view as a key performance indicator for warehouse and logistic departments. The delivery performance indicated how effective the supply chain is at supplying products to the customer and the customer satisfaction level. Present research is focused on a case study conducted in a flour mill in Malaysia. In this study, the importance is highlighted and the causes of the delivery issues are investigated. For this study, in-depth interview was carried out and data was analysed from the flour mill to investigate the issues.